2023
DOI: 10.1038/s42003-023-04847-6
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-induced tau amyloid fibrils

Abstract: The intrinsically disordered protein tau aggregates into β-sheet amyloid fibrils that spread in human brains afflicted with Alzheimer’s disease and other neurodegenerative diseases. Tau interaction with lipid membranes might play a role in the formation and spreading of these pathological aggregates. Here we investigate the conformation and assembly of membrane-induced tau aggregates using solid-state NMR and transmission electron microscopy. A tau construct that encompasses the microtubule-binding repeats and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 90 publications
(104 reference statements)
0
7
0
Order By: Relevance
“…When OptoTau was expressed, the confinement length of EGFR diffusion extended regardless of the tau aggregation. Previous studies suggested a direct interaction of both soluble and filamentous tau protein with the plasma membrane especially lipid raft [28,29]. The confinement region for the slow-mobile state was indicated to correspond to a membrane subdomain [1], and the size of which is similar to a lipid raft.…”
Section: Effect Of Tau Aggregation On Receptor Mobilitymentioning
confidence: 83%
“…When OptoTau was expressed, the confinement length of EGFR diffusion extended regardless of the tau aggregation. Previous studies suggested a direct interaction of both soluble and filamentous tau protein with the plasma membrane especially lipid raft [28,29]. The confinement region for the slow-mobile state was indicated to correspond to a membrane subdomain [1], and the size of which is similar to a lipid raft.…”
Section: Effect Of Tau Aggregation On Receptor Mobilitymentioning
confidence: 83%
“…Furthermore, previous studies have established that tau proteins interact with membrane lipids, crucial in AD and other neurodegenerative disorders. 50 Therefore, the observed expression of AT8 due to SARS-CoV-2 infection suggests a potential link between SARS-CoV-2 infection and AD. In this study, we have found reasonable evidence for increased tau pathology during SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 95%
“…Within intrinsically disordered proteins, lipid-binding occurs in more structured regions, such as the relatively more ordered repeat region in tau where its prion properties reside 62 . Indeed, using solid-state NMR and transmission electron microscopy, a tau construct encoding the microtubule-binding repeats and a proline-rich domain was reconstituted into cholesterol-containing phospholipid membranes in a transition from a random coil to a β-sheet conformation over weeks 63 . Cellular aggregates displayed colocalization with VCP and SQSTM1, proteins essential for aggresome formation and selective autophagy 4749,53,64 .…”
Section: Discussionmentioning
confidence: 99%